Prospective cohort study of febrile neutropenia in breast cancer patients administered with neoadjuvant and adjuvant chemotherapies: CSPOR-BC FN study. (April 2021) - Ishikawa, Takashi; Sakamaki, Kentaro; Narui, Kazutaka; Nishimura, Hideki; Sangai, Takafumi; Tamaki, Kentaro; Hasegawa, Yoshie; Watanabe, Ken-ichi; Suganuma, Nobuyasu; Michishita, Shintaro; Sugae, Sadatoshi; Aihara, Tomohiko; et al.
Abstract: Background: As Asians are more vulnerable to febrile neutropenia (FN) than Caucasians, evaluations of FN incidence and risk factors in Asians are important for the appropriate use of primary pegfilgrastim (PEG-G). Patients and methods: Japanese breast cancer patients receiving standard adjuvant chemotherapies were prospectively enrolled in multicenter institutions from August 2015 to July 2017. FN was evaluated from 2 treatment policies: true FN (T-FN): ≥37.5 °C, grade 4 neutropenia, mandatory hospital visit (visiting); surrogate FN (S-FN): ≥37.5 °C, oral antibiotic, no mandatory visit (non-visiting). PEG-G was used at the physicians' discretion. The primary endpoint was FN incidence during all cycles. Multivariate logistic regression analysis was performed to identify T-FN risk factors. Results: Of 1005 enrolled patients, 980 women treated with FEC, E(A)C, and TC were analyzed. The FN incidence proportions in all patients were 22.5%, 27.5%, and 33.9% for FEC, E(A)C, and TC, respectively. Those of T-FN were 27.7%, 22.4%, and 36.6%; those of S-FN were 17.3%, 32.4%, and 31.5% with more frequent primary PEG-G usage. The relative dose intensity (RDI) of the 3 regimens was ≥0.85 in both groups. In the analysis of risk factors, TC (odds ratio = 2.67), age ≥ 65 years (2.24), and pretreatment absolute neutrophil count (ANC)/1000 μl (0.8) remained significant. Conclusions: FN incidences were above 20% in the 3 regimens, with TC showing the highest. RDI was maintained at a high level in both visiting and non-visiting groups. Patient-related risk factors were age and pretreatment ANC. Highlights: This study compared febrile neutropenia (FN) incidences of 3 breast cancer regimens. FN incidences were >20% in the 3 regimens (FEC, E(A)C; TC); TC showed the highest. The relative dose intensities in visiting and non-visiting groups were at high level. Age and pretreatment absolute neutrophil count were found as significant FN factors.